2005
DOI: 10.1287/orsc.1050.0132
|View full text |Cite
|
Sign up to set email alerts
|

Building Organization Theory from First Principles: The Self-Enhancement Motive and Understanding Power and Influence

Abstract: I n developing and advancing organization theory, it is useful if we can uncover fundamental constructs that can then be used to integrate larger areas of inquiry, even as we continue to accumulate more knowledge, evidence, and concepts. However, accomplishing this will require a somewhat different approach to theory building and testing. We illustrate the process of building an integrated model from fundamental constructs by using the idea of self-enhancement to explore phenomena of power and influence. We ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 88 publications
5
132
0
1
Order By: Relevance
“…To preserver power, high power individuals often look for traits or characteristics in others that they can construe as justifying their disproportionate amount of power (e.g., Goodwin, Gubin, Fiske, & Yzerbyt, 2000;Goodwin, Operario, & Fiske, 1998). Because the desire to maintain power is driven in part by self-enhancement (Pfeffer & Fong, 2005), an affront to the self-esteem of high power individuals is likely to result in the powerholder experiencing feelings of aggression toward the source of the threat (Fast & Chen, 2009). …”
Section: The Role Of Advisor Experience and Expertisementioning
confidence: 99%
“…To preserver power, high power individuals often look for traits or characteristics in others that they can construe as justifying their disproportionate amount of power (e.g., Goodwin, Gubin, Fiske, & Yzerbyt, 2000;Goodwin, Operario, & Fiske, 1998). Because the desire to maintain power is driven in part by self-enhancement (Pfeffer & Fong, 2005), an affront to the self-esteem of high power individuals is likely to result in the powerholder experiencing feelings of aggression toward the source of the threat (Fast & Chen, 2009). …”
Section: The Role Of Advisor Experience and Expertisementioning
confidence: 99%
“…Personal power is likely to be inversely related to pressure. An individual that is high in power feels in control of his or her outcomes and is less susceptible to external pressure (Pfeffer and Fong, 2005). Power tends to reduce the threat of losses (Inesi, 2010) which alters the motivational mechanisms within individuals.…”
Section: Power and The Decision To Commit Financial Statement Fraudmentioning
confidence: 99%
“…Singer (1991) reported that a closed list of leadership attributes did not account for the observed variance in the leadership aspirations of individuals. A possible explanation for the lack of significance was that the specific attributes on the closed list might not be relevant to all participants (Pfeffer & Fong, 2005). She suggested that idiographic approaches that capture significant leadership attributes might be more appropriate.…”
Section: Methodsmentioning
confidence: 99%